Local scour downstream of a weir - Win, Yone Yone (Nanyang Technological University, 2023)
The present study explores the complex phenomena of scouring downstream of a weir, specially focusing on the maximum scour depth caused by two distinct sand diameters. The study aims to extend previous research and develop equations, grounded in empirical data, to accurately predict the maximum scour depth. The parameters analysed include the weir height, flow rate, tailwater depth and median sand size. This research utilizes a systematic experimental setup, employing a hydraulic flume in a laboratory setting to simulate the weir flow conditions and record via webcam the scour formation downstream of the weir. The study extends the scope by examining the scour depth using two median sediment sizes of 0.77mm and 4.75mm. The latter large sediment size has not been tested so far. The primary findings indicate that an increase in flow rate and a decrease in tailwater depth result in a broader and deeper scour formation. The inclusion of an apron was observed to significantly diminish the scour depth while having a negligible effect on the scour length. Furthermore, changes in sediment size were found to have a direct impact on the dimensions of the scour hole. Based on these results, a regression analysis was performed to formulate prediction equations for the maximum scour depth, taking into account the correlating parameters. The outcomes from these prediction equations for maximum scour depth has an error margin of ± 30%, which is deemed adequately reliable to estimate the scour downstream of a weir for practical purposes.